The Relationship Between Parity and Type of Labor with Incidence of Postpartum Blues - Rowi, Laily Alfajriatu; Sholikah, Siti Mar'atus; Kusumaningtyas, Kharisma; Sukesi, Sukesi (JURNAL KEBIDANAN, 2024)
Postpartum blues refer to mood disorders that occur a few days after labor to about two weeks with a peak of instability on days 3 to 5. In 2020, the prevalence of postpartum blues in Indonesia reached 50-70%. This research is an analytical survey using a cross-sectional design. The population in this research consisted of 127 respondents. The research sample was 97 respondents selected through purposive sampling. The variables in this study include independent variables such as parity and type of labor, and the dependent variable is the incidence of postpartum blues. The instrument used was a questionnaire. The analysis of the relationship between variables was done using the chi-square test. The research results indicate that the majority of postpartum mothers (53,6%) were multiparity mothers. The majority of postpartum mothers (68,4%) gave birth by sectio caesaria.  The majority of postpartum mothers (56,7%) experienced the postpartum blues. The chi-square test results indicate that there was a relationship between parity with the incidence of postpartum blues with a p-value of 0.010 α 0.05 and also a relationship between the type of labor with the incidence of postpartum blues with a p-value of 0.004 α 0.05. Based on the description above, it can be concluded that there is a relationship between parity and type of labor with the incidence of postpartum blues. The role of the midwife is necessary to provide support to postpartum mothers so that they can adapt well and accept their new role as a mother.